Prevalence and identification of arthropod-transmitted viruses in Kassala state, Eastern Sudan. Issue 1 (1st January 2019) - Mohamed, Nahla; Magzoub, Mamoun; Mohamed, Rania El Hadi; Aleanizy, Fadilah Sfouq; Alqahtani, Fulwah Y.; Nour, Bakri Y. M.; Alkarsany, Mubark M.S.
ABSTRACT: Vector-borne diseases are responsible for more than 20% of the infectious diseases worldwide. The prevalence of arboviruses transmit diseases to humans in Sudan has not been investigated. Mosquito-borne viral diseases increase globally incidence, including the Sudan. Frequent unknown fever outbreaks have been reported in eastern region, Sudan. However, diagnosis was based exclusively on clinical signs and symptoms without confirmatory laboratory investigations. However, for accurate detection of these viruses in outbreaks, molecular technique is considered. The objective of this study was to determine the prevalence of six arboviruses in the Kassala state of east Sudan during unknown fever outbreak. A cross sectional hospital-based study was conducted in the Kassala, Teaching Hospital. Blood samples from 119 patients suffering from unknown fever were used for screening of six arboviruses, hepatitis E virus and malarial using molecular techniques and serology.  The overall arboviruses seroprevelance was 61.3% (73/119). The highest positivity rate was 73.1% (52/73) chikungunya virus; 29 males and 20 females patients were chikungunya positive. Other arboviruses were circulating in low rate 20.5% (15/73), and 6.8% (5/73) for sindbis and rift valley fever viruses respectively. Hepatitis E virus was negative in all cases and malaria positivity rate 13.4% (16/119). The prevalence of arboviruses among unknown fever patients present to Kassala teaching hospital of eastern region in Sudan is significantly high (61.3%). The chikungunya virus is the predominant causative agent of arboviruses. Molecular techniques such as PCR are important for accurate and rapid diagnosis of this viral outbreak.